Analisis Ekokritik pada Novel “Coretan-Coretan Sunyi” Karya Ngangga Saputra - Muhammad Yunus R.H; Agik Nur Efendi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research aims to describe the environmental damage that occurs in the interior of Central Kalimantan as contained in the novel Coretan-Coretan Sunyi by Ngangga Saputra, using Greg Garrard's ecocritical theory. This research uses a qualitative descriptive method. Qualitative research is research that has the aim of understanding events that are happening and describing them in words. This research data collection technique uses listening and note-taking techniques. This research's data analysis technique has three stages, (1) recording data related to ecocriticism such as environmental damage in the novel; (2) presenting and arranging data according to Greg Garrard's theory; (3) draw conclusions and adjust the data. The results of this research are the living conditions of people in the interior of Central Kalimantan (1) busy gold mines with the sound of machines; (2) the fate of future generations who inherit mining waste; (3) rural children who are educated to continue their parents' gold mining business. There are also impacts of environmental damage in the interior, namely, (1) environmental conditions that have been damaged; (2) the richness of the former inland forests; (3) waste that pollutes the environment; (4) pollution of the Kahayan River; and (5) there is no clean water in the interior due to rivers being polluted by company waste. The findings in this research serve as a reflection for us to preserve the environment and study environmental values ​​in literary works